Tragedy revisited - Boyd, R.; Richerson, P. J.; Meinzen-Dick, Ruth S.; Moor, T. de; Jackson, M.O.; Gjerde, K.M.; Harden-Davies, Harriet; Frischmann, B.M.; Madison, M.J.; Strandburg, K.J.; McLean, A.R.; Dye, C. (American Association for the Advancement of Science, 2018)
“Freedom in a commons brings ruin to all.” So argued ecologist Garrett Hardin in “The Tragedy of the Commons” in the 13 December 1968 issue of Science (1). Hardin questioned society's ability to manage shared resources and avoid an environmentally and socially calamitous free-for-all. In the 50 years since, the essay has influenced discussions ranging from climate change (see page 1217) to evolution, from infectious disease to the internet, and has reached far beyond academic literature—but not without criticism. Considerable work, notably by Nobelist Elinor Ostrom (2), has challenged Hardin, particularly his emphasis on property rights and government regulatory leviathans as solutions. Instead, research has documented contexts, cases, and principles that reflect the ability of groups to collectively govern common resources. To mark this anniversary and celebrate the richness of research and practice around commons and cooperation, Science invited experts to share some contemporary views on such tragedies and how to avert them. —Brad Wible